Exogenous Let-7a-5p Induces A549 Lung Cancer Cell Death Through BCL2L1-Mediated PI3Kγ Signaling Pathway - Duan, Shuyin; Yu, Songcheng; Yuan, Teng; Yao, Sanqiao; Zhang, Lin (Frontiers in Oncology, 2019)
Elevated expression of let-7a-5p contributes to suppression of lung cancer, in which let-7a-5p, as exosome cargo, can be transported from macrophages to lung cancer cells, yet the role of let-7a-5p remains unclear. Utilizing bioinformatics methods and cellular experiments, this study was designed and conducted to identify let-7a-5p regulatory network in lung cancer. Bioinformatics analysis and Kaplan-Meier survival analysis revealed that let-7a-5p could directly target BCL2L1, and aberrant expression of let-7a-5p affects the survival of lung cancer patients, which was confirmed in A549 lung cancer cells using luciferase reporter assay. Moreover, let-7a-5p inhibited BCL2L1 expression and suppressed lung cancer cell proliferation, migration, and invasion. Functionally, overexpression of let-7a-5p promoted both autophagy and cell death in A549 lung cancer cells through PI3Kγ signaling pathway, whereas the apoptosis and pyroptosis of A549 lung cancer cells were unaffected. Furthermore, aberrant expression of BCL2L1 significantly altered the expression of lung cancer biomarkers such as MYC, EGFR, and Vimentin. To sum up, these data demonstrate that exogenous let-7a-5p induces A549 lung cancer cell death through BCL2L1-mediated PI3Kγ signaling pathway, which may be a useful target for lung cancer treatment.